Fenomena aliran melintasi empat buah silinder sirkular yang tersusun in line square - Manuels, Arif; Cut, Banta; Arif, Zainal (JURUTERA - Jurnal Umum Teknik Terapan, 2025)
The development and application of circular cylinders are extensively used in various fields of engineering. These applications include the construction of offshore support pipelines, subsea pipeline networks, and shell-and-tube heat exchangers. Previous research has consistently shown that drag force, lift force, and vortex shedding occur when fluid flows past these cylinder arrangements. Consequently, further investigations have been conducted through numerical simulations, primarily aiming to mitigate these undesirable phenomena of drag, lift, and vortex shedding within the circular cylinder arrangements. This particular study focuses on four circular cylinders arranged in an in-line square configuration. The main cylinder diameter (D) is 25 mm, while the diameter of the disturbing body (BP) (d) is 4 mm, resulting in a diameter ratio (d/D) of 0.16. This cylinder arrangement was positioned within a narrow square channel with cross-sectional dimensions of H = 300 mm and L = 1500 mm. The setup had a blockage ratio of 25% and was tested at a Reynolds number (Re) of 5.0×104, based on the cylinder diameter. For the study, three variations of Inlet Disturbance Bodies (IDB) were placed at angles of 0o, 90o, and 270o in front of the two upstream cylinders, maintaining a gap ratio (G/D) of 0.16 relative to the circular cylinders. This numerical simulation research was carried out using 2D Unsteady-RANS via Ansys Fluent Student R2021 software. A structured mesh was employed for meshing, and the k-ω-SST model was selected for turbulence modeling. The findings of this research indicate that both the distance (L/D) and the implementation of three IDBs significantly influence the drag coefficient observed on the four circular cylinders arranged in an in-line square formation. Specifically, the addition of three IDBs around the two upstream cylinders at angles of 0o, 90o, and 270o proved to be highly effective in reducing the drag coefficient (CD) on cylinder 3 (downstream top) and cylinder 4 (downstream bottom).